Beliefs about medicine and illness are associated with fear of cancer recurrence in women taking adjuvant endocrine therapy for breast cancer. (8th November 2012) - Corter, Arden L.; Findlay, Michael; Broom, Reuben; Porter, David; Petrie, Keith J.
<x xml:space="preserve">Abstract</x> Objectives Adjuvant endocrine therapy for early‐stage breast cancer has greatly reduced the morbidity and mortality associated with breast cancer recurrence. Despite this, a significant proportion of women report fears of cancer recurrence. This study examined the associations between fear of cancer recurrence (FoR) and illness perceptions, medication beliefs, and treatment side effects in women taking adjuvant endocrine therapy following breast cancer. Methods A total of 153 post‐menopausal women with early‐stage breast cancer completed a postal survey. Analyses were conducted to examine the association between FoR and illness perceptions, medication beliefs, treatment side effects, demographic factors, and emotional distress and to identify which of these factors would be most strongly associated with FoR in a regression model. Results All illness perceptions (apart from personal control) were associated with FoR, as were patient beliefs about endocrine therapy. Although treatment side effects, being unemployed, and higher levels of anxiety and depression were associated with FoR, only illness perceptions (identity, treatment control, timeline, and emotional representation) and medication necessity beliefs were significantly correlated with FoR in the final model. Conclusions It appears that, in addition to directly targeting FoR, it may be worthwhile to address the illness and medication beliefs supporting the fear. Additionally, helping women to differentiate everyday symptoms from those indicative of breast cancer may help to reduce fear of recurrence. Statement of Contribution What is already known on this subject? A significant proportion of women report fear of cancer recurrence following breast cancer. The literature shows that illness perceptions, side effects of treatment, and beliefs about medicines are related to fear of recurrence among cancer patients. However, because these variables have often been looked at in isolation, it is not clear whether some perceptions or cues are more likely to relate to fear of recurrence than others. What does this study add? This study shows illness perceptions and medication beliefs are strongly related to fears of cancer recurrence. The results point to ways in which the self‐regulatory model of illness may be used to reduce patients' fear of recurrence. The study results show that women with higher fear of recurrence may be balancing a tension between believing that they need to take the medication to protect their future health alongside concerns that the treatment may not be working.